Dietary Variation of Long Tailed Macaques (Macaca fascicularis) in Telaga Warna, Bogor, West Java - SARAH NILA; BAMBANG SURYOBROTO; KANTHI ARUM WIDAYATI (Bogor Agricultural University, Indonesia, 2014)
The genus Macaca, member of sub-family Cercopithecinae, is the most widely distributed non-human primates in Asian countries. The habitats are strongly influence the dietary variation of the populations. The dietary variation of the macaques reflect ecological plasticity in coping with differences both in availability and abundance of food. The macaques are plastic in taking any kind of food that available in their home range and adjust their behaviour according to its abundance. Here, we present the dietary variation of long-tailed macaques (Macaca fascicularis) in the high altitude rain forest of Telaga Warna, West Java, Indonesia. The proportion of their food from natural sources is greater than those from visitors. The natural food consisted of plants, small animals (insects and earthworm), fungi and water from lake. The plant food comprised of 29 species plus a few mosses. The frequency of eating artificial food was influenced by visitors who come for picnic. In this site, the macaques learned that the visiting of tourists is identical with food.